The Effect of Education Background and Work Experience on Employee Ethics at PT. Timbang Deli Indonesia - Lilis Ikawati Ramadhani; Lidiya Yunita Simanjuntak (Institute of Computer Science (IOCS), 2020)
This research was conducted to find out how much influence educational background and work experience have on the work ethic of employees at PT. Timbang Deli Indonesia, and also what factors support the improvement of employee work ethics in addition to educational background and work experience. This study took samples from employees of PT. Timbang Deli Indonesia, which predominantly were high school graduated with age between 28-37 years, as many as 139 people. Primary data obtained from the questionnaire that has been filled in by employees of PT. Timbang Deli Indonesia were used as the sample in this study. The results of this study indicate that the independent variables, namely educational background (X1) and work experience (X2), have a positive and significant effect on the work ethic of employees at PT. Timbang Deli Indonesia. Moreover, from the results of multiple linear regression analysis, it can be concluded that (1) the educational background variable has a positive and significant effect on the work ethic variable, with β coefficient of educational background is negative at 6,033> 1,977, (2) the work experience variable has a positive and significant effect on the work ethic variable, with positive coefficient β value 3.067> 1.977, and (3) together these showed that the educational background and work experience variables significantly influence the work ethic variable of the employees of PT. Timbang Deli Indonesia with a F value of 49.527 and a significance level of 0.000.